Genetic and clinical characteristics of NEFL-related Charcot-Marie-Tooth disease. Issue 7 (13th May 2017) - Horga, Alejandro; Laurà, Matilde; Jaunmuktane, Zane; Jerath, Nivedita U; Gonzalez, Michael A; Polke, James M; Poh, Roy; Blake, Julian C; Liu, Yo-Tsen; Wiethoff, Sarah; Bettencourt, Conceição; Lunn, Michael PT; et al.
Abstract : Objectives: To analyse and describe the clinical and genetic spectrum of Charcot-Marie-Tooth disease (CMT) caused by mutations in the neurofilament light polypeptide gene ( NEFL ). Methods: Combined analysis of newly identified patients with NEFL -related CMT and all previously reported cases from the literature. Results: Five new unrelated patients with CMT carrying the NEFL mutations P8R and N98S and the novel variant L311P were identified. Combined data from these cases and 62 kindreds from the literature revealed four common mutations (P8R, P22S, N98S and E396K) and three mutational hotspots accounting for 37 (55%) and 50 (75%) kindreds, respectively. Eight patients had de novo mutations. Loss of large-myelinated fibres was a uniform feature in a total of 21 sural nerve biopsies and 'onion bulb' formations and/or thin myelin sheaths were observed in 14 (67%) of them. The neurophysiological phenotype was broad but most patients with E90K and N98S had upper limb motor conduction velocities <38 m/s. Age of onset was ≤3 years in 25 cases. Pyramidal tract signs were described in 13 patients and 7 patients were initially diagnosed with or tested for inherited ataxia. Patients with E90K and N98S frequently presented before age 3 years and developed hearing loss or other neurological features including ataxia and/or cerebellar atrophy on brain MRI. Conclusions: NEFL -related CMT is clinically and genetically heterogeneous. Based on this study, however, we propose mutational hotspots and relevant clinical–genetic associations that may be helpful in the evaluation of NEFL sequence variants and the differential diagnosis with other forms of CMT.